2017
DOI: 10.1007/s00415-017-8614-9
|View full text |Cite
|
Sign up to set email alerts
|

Recalling feature bindings differentiates Alzheimer’s disease from frontotemporal dementia

Abstract: It has been challenging to identify clinical cognitive markers that can differentiate patients with Alzheimer's disease (AD) from those with behavioral variant frontotemporal dementia (bvFTD). The short-term memory binding (STMB) test assesses the ability to integrate colors and shapes into unified representations and to hold them temporarily during online performance. The objective of this study is to investigate whether free recall deficits during short-term memory binding (STMB) test can differentiate patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 42 publications
3
36
0
2
Order By: Relevance
“…Whether age spares the ability to freely recall bound features held in short-term memory (STM) remains unexplored. This is relevant because a free recall version of the STMB test has been used previously to compare performance of healthy and cognitively impaired older adults (Cecchini et al, 2017;Della Sala et al, 2012;Parra, Abrahams, Fabi, et al, 2009). These studies with clinical samples reported very similar results to those obtained with the visual recognition (change detection) version of the STMB test.…”
Section: Introductionmentioning
confidence: 77%
“…Whether age spares the ability to freely recall bound features held in short-term memory (STM) remains unexplored. This is relevant because a free recall version of the STMB test has been used previously to compare performance of healthy and cognitively impaired older adults (Cecchini et al, 2017;Della Sala et al, 2012;Parra, Abrahams, Fabi, et al, 2009). These studies with clinical samples reported very similar results to those obtained with the visual recognition (change detection) version of the STMB test.…”
Section: Introductionmentioning
confidence: 77%
“…The deficit occurs in both sporadic AD and familial AD caused by a specific genetic mutation, as well as in asymptomatic carriers of the mutation (Liang et al ., ; Parra, Abrahams, Logie, & Della Sala, ). This binding deficit has been proposed as a diagnostic tool since it allows differentiation between AD and other forms of dementia and clinical conditions (Cecchini et al ., ; Della Sala, Parra, Fabi, Luzzi, & Abrahams, ; Liang et al ., ; Parra, ; Parra, Abrahams, Logie, & Della Sala, ).…”
Section: Binding In Ageing and Clinical Conditionsmentioning
confidence: 99%
“…There are memory functions the decline of which could be detected prior to the dementia stage of AD (e.g., temporary binding abilities). These memory functions have proved both sensitive and specific to AD (Cecchini et al, 2017;S. Della Sala et al, 2012;.…”
Section: Why Dissecting Memory Binding Impairments Is Important?mentioning
confidence: 99%